Strategi Pengembangan Startup Digital di Pontianak Dengan Pendekatan Design Thinking - Andriyati, Lailatul; Ellya Zulaikha (STEKOM PRESS, 2023)
Abstract Startups are designed to find the right business model to make the business survive. Startups have the possibility to succeed or fail. This is influenced by capabilities in digital transformation and business development in the technology sector. Indonesia has a low number and quality of digital talent and low entrepreneurship (3.1%). Pontianak has the least number of digital startups (0.74%). Every part in the digital ecosystem is very influential on the sustainability of digital startups. The digital ecosystem in Pontianak is the government, accelerators, universities, incubators, students/talent, communities, and digital startups. This research aims to help digital ecosystems overcome difficulties in collaborating for the development of digital startups in Pontianak. The research method is direct surveys and interviews with 6 local digital startups and startup stakeholders in Pontianak. Stakeholder analysis to determine respondents. The results of in-depth interviews were analyzed using design thinking and focus group discussion (FGD) methods. The results of the research are the main factor for overcoming difficulties in collaborative digital startup development in Pontianak: 1) digital ecosystem activation; and 2) digital-sociopreneurship development and competency improvement. The recommended startup development strategy aims to realize these two things.